2008
DOI: 10.2166/wst.2008.147
|View full text |Cite
|
Sign up to set email alerts
|

Activated sludge process monitoring through in situ near-infrared spectral analysis

Abstract: The application of near infrared (NIR) spectroscopy for industrial process monitoring is achieving increasing importance over the last twenty years. In fact, the real time monitoring capacity of NIR spectroscopy is a very important feature for process monitoring, prediction and control as it allows a fast evaluation of the state of the process. However, the application of NIR spectroscopy in wastewater treatment processes is still to be explored. Although some applications of the technique for wastewater monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 16 publications
0
13
0
1
Order By: Relevance
“…NIRS has been shown to successfully measure oil, urea, methanol and glycerol concentrations and solids content of the waste water discharge from biodiesel fuel production processes [20,21]. Preliminary work by Dias et al [19] supports the use of NIRS as an on-line quality monitoring tool for activated sludge reactors to detect changes in the feed influent. These are only a few of the many potential applications of NIRS as a tool in agriculture, waste water and environmental management.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…NIRS has been shown to successfully measure oil, urea, methanol and glycerol concentrations and solids content of the waste water discharge from biodiesel fuel production processes [20,21]. Preliminary work by Dias et al [19] supports the use of NIRS as an on-line quality monitoring tool for activated sludge reactors to detect changes in the feed influent. These are only a few of the many potential applications of NIRS as a tool in agriculture, waste water and environmental management.…”
Section: Introductionmentioning
confidence: 99%
“…The real-time monitoring capacity of NIRS is a very important feature for the application to industrial process and waste water monitoring, prediction and control as it would allow fast evaluation of the state of the process [19]. NIRS has been shown to successfully measure oil, urea, methanol and glycerol concentrations and solids content of the waste water discharge from biodiesel fuel production processes [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…Partial least squares (PLS) is a widely used statistical technique able to model a given predicted variable and detect deviations [19]. Furthermore, PLS models have been recently used for the estimation of COD, nitrate (NO 3 À ), total organic carbon (TOC), and mixed liquor suspended solids (MLSS) using ultraviolet-visible and near-infrared spectroscopy on wastewater treatment systems [20][21][22]. Despite the prior use of image analysis data, coupled to PLS models, to estimate sludge volume index (SVI) and MLSS [11,12,15], QIA has not yet been applied, to our knowledge, neither to estimate the COD removal ability nor nitrification/denitrification occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…The studies found represent quite diverse applications, for instance, quantitative measurements of oil, urea and solids [5], glycerol [6], and methanol and glycerol simultaneously [7] in wastewater from a biodiesel fuel production plant. As another example, in one of the few in-situ applications found [8], principal component analysis (PCA) was used instead of quantitative modelling to monitor an activated sludge plant.…”
Section: Introductionmentioning
confidence: 99%